Effect of Graphene Nanosheets on the Morphology, Crystallinity, and Thermal and Electrical Properties of Super Tough Polyamide 6 Using SEBS Compounds - Farzaneh Alirezaei Hoor; Jalil Morshedian; Shervin Ahmadi; Mohammad Rakhshanfar; Alireza Bahramzadeh (Journal of Chemistry)
Super tough polyamide 6 was prepared by using SEBS and effect of SEBS-g-MA as a compatibilizer of PA6/SEBS matrix on mechanical properties was investigated. Thus super tough polyamide 6/graphene nanocomposites were produced using graphene nanosheets (GNs) through the melt compounding method. To compare the effectiveness of graphene, effects of graphite and carbon black (the other carbon structures) are also studied on the same matrix. The effects of graphene on crystallinity, improvements of morphology, and thermal and electrical properties of the nanocomposites were researched and compared with similar samples of graphite and carbon black. Due to the reaction between the maleic anhydride groups of SEBS and amine groups of nylon chains during the melt mixing process, super tough polyamide 6 was produced with high impact and tensile strength. The most important results of this study can be noted as an increase in the electrical conductivity and thermal stability by adding graphene to PA6/SEBS blend. Also the effect of graphene compatibility on PA6/SEBS/SEBS-g-MA blend was investigated with studying morphology.